Software Engineering and Formal Methods 9th International Conference, SEFM 2011, Montevideo, Uruguay, November 14-18, 2011. Proceedings - Barthe, Gilles; Pardo, Alberto; Schneider, Gerardo; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Software Engineering and Formal Methods, SEFM 2011, held in Montevideo, Uruguay, in November 2011. The 22 revised regular papers presented together with 1 short paper, 2 tool papers, and 4 keynote talks were carefully reviewed and selected from 105 initial abstracts and 85 full submissions. Besides the regular session the conference held a special track devoted to "Modeling for Sustainable Development" with 5 accepted papers - selected from 7 submissions - that are also part of this volume. The aim of SEFM is to advance the state of the art in formal methods, to scale up their application in software industry and to encourage their integration with practical engineering methods.
Electronic reproduction.
Keywords: Software engineering -- Congresses; Formal methods (Computer science) -- Congresses; Electronic book